Acid Phosphatase Activity in Relation to Reproductive Behaviour in Males of Antheraea mylitta Drury During Different Development Stages and Impact of use of Male Moth for Repeated Mating - Lokesh G.; Srivastava A.K.; Srivastava P.P.; Kar P.K.; Sinha A.K.; Sahay Alok (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Comparative Acid phosphatase (ACP) activity was studied in two ecoraces of Antheraea mylitta viz., Daba and Laria during different developmental stages of lifecycle to analyze the reproductive behavior of the male tasar silkworm and also the effect of repeated use of male moths for mating. It was found that higher protein concentration was recorded in the pupal hemolymph of both the tasar silkworm races i.e., Daba (135.33± 3.21mg/ml) and Laria (131± 3.60 mg/ml) compared to testis. Also an increased protein concentration was recorded in the testis tissue from the larval stage to moth before coupling. Higher ACP activity was found in the testis tissue of the moth (55.2 ± 1.92 µg p-nitrophenol/mg protein/hr) followed by pupal hemolymph with similar trend in both the ecoraces studied but comparatively low activity in the Laria. Fecundity and hatching was affected when the male moths were used for second mating. About 6-8% reduction in the fecundity and 10-16% in hatching was observed. Also difficulty of mating and needs hand coupling method to establish the mating. Hence, second time using of males during scarcity and in exigent cases is suggested to improve total layings in the grainages to meet the demand.